2022
DOI: 10.3389/fmolb.2022.972146
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical characterization of population dynamics in breast cancer cells treated with doxorubicin

Abstract: The development of chemoresistance remains a significant cause of treatment failure in breast cancer. We posit that a mathematical understanding of chemoresistance could assist in developing successful treatment strategies. Towards that end, we have developed a model that describes the cytotoxic effects of the standard chemotherapeutic drug doxorubicin on the MCF-7 breast cancer cell line. We assume that treatment with doxorubicin induces a compartmentalization of the breast cancer cell population into survivi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…The copyright holder for this preprint (which this version posted June 2, 2024. ; https://doi.org/10.1101/2024.05.28.596337 doi: bioRxiv preprint perturbations skewing interpretation of bulk results. Subpopulations have been characterized in cell lines through different modalities [27][28][29][30]35,45,46 , but these studies may have isolated rare subsets of cells. In contrast, clusterCleaver delivers a workflow for discovering and isolating subpopulations starting from full knowledge of the transcriptomic diversity within cell lines by starting at scRNA-seq.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The copyright holder for this preprint (which this version posted June 2, 2024. ; https://doi.org/10.1101/2024.05.28.596337 doi: bioRxiv preprint perturbations skewing interpretation of bulk results. Subpopulations have been characterized in cell lines through different modalities [27][28][29][30]35,45,46 , but these studies may have isolated rare subsets of cells. In contrast, clusterCleaver delivers a workflow for discovering and isolating subpopulations starting from full knowledge of the transcriptomic diversity within cell lines by starting at scRNA-seq.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been performed on cell lines without knowledge of their underlying population structure, yet subpopulations of cells may behave disparately under different culture conditions and perturbations skewing interpretation of bulk results. Subpopulations have been characterized in cell lines through different modalities 2730,35,45,46 , but these studies may have isolated rare subsets of cells. In contrast, clusterCleaver delivers a workflow for discovering and isolating subpopulations starting from full knowledge of the transcriptomic diversity within cell lines by starting at scRNA-seq.…”
Section: Discussionmentioning
confidence: 99%
“…Another predator-prey mathematical model showed evidence of reciprocal antagonism at play within competition dynamics of parental and radiation-resistant cell lines [24]. These models have also been applied to endocrine therapy [25] and doxorubicin therapy [26,27] in breast cancer cell lines. There is also evidence of the existence of positive or cooperative ecological interactions in cancer: one recent study indicated paracrine signaling as a mechanism for which the dominant cell line's growth is enhanced by the presence of a co-cultured second cell line [28].…”
Section: Measuring Effective Games In Oncologymentioning
confidence: 99%
“…Therefore, targeting drug resistance in breast cancer is crucial. 4 Mechanisms of DOX resistance are multifaceted and include upregulation of drug-resistant proteins, changes in membrane permeability of cancer cells, impairment of DNA damage repair mechanisms, and autophagy-arbitrated drug resistance. 5 Among these mechanisms, autophagy-mediated chemotherapy resistance has gained increasing attention.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, about 30–50% of metastatic breast cancer patients are irresponsive to the DOX treatment. Therefore, targeting drug resistance in breast cancer is crucial …”
Section: Introductionmentioning
confidence: 99%